Metabolic dysregulation in first-episode schizophrenia patients with respect to genetic variation in one-carbon metabolism. (30th April 2016) - Misiak, Błażej; Łaczmański, Łukasz; Słoka, Natalia Kinga; Szmida, Elżbieta; Piotrowski, Patryk; Loska, Olga; Ślęzak, Ryszard; Kiejna, Andrzej; Frydecka, Dorota
Abstract: The aim of this study was to investigate the prevalence of metabolic disturbances in patients with first-episode schizophrenia (FES) and test the hypothesis that genetic variation in one-carbon metabolism may account for metabolic dysregulation in early psychosis. We measured fasting glucose, lipid profile parameters, homocysteine, folate and vitamin B12 in 135 patients with FES and 146 healthy controls (HCs). Polymorphisms in the following genes were determined: MTHFR (C677T and A1298C), MTHFD1 (G1958A), MTRR (A66G) and BHMT (G742A). Serum levels of folate and high-density lipoproteins (HDL) were significantly lower in patients with FES compared to HCs. In turn, serum levels of homocysteine and triglycerides were significantly higher in patients with FES than in HCs. Prevalence of hyperhomocysteinemia, low folate and HDL levels together with dyslipidemia was significantly higher in patients with FES compared to HCs. Higher homocysteine levels, lower vitamin B12 levels and the presence of metabolic syndrome were associated with higher severity of negative symptoms. None of studied polymorphisms was associated with schizophrenia risk. Several associations between studied polymorphisms and cardio-metabolic parameters were found. None of them remained significant after Bonferroni correction. Our results indicate that metabolic dysregulation in patients with FES is not associated with genetic variation in one-carbon metabolism. Highlights: A number of metabolic disturbances are highly prevalent in first-episode schizophrenia. Metabolic dysregulation in first-episode schizophrenia might be clinically relevant. Studied gene polymorphisms are not related to metabolic changes in early psychosis.